Tingkatkan Kemampuan Berpikir Kritis dan Hasil Belajar Biologi dengan Kombinasi Model Inkuiri Terbimbing dan Numbered Heads Together - Nuzuliya, Firdausi (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2024)
The results of observations and interviews with Biology teachers of class X3 MA Maarif Sukorejo showed that the current learning method is not effective in improving critical thinking skills and students’ cognitive learning outcomes. This study applies a guided inquiry model combined with Numbered Heads Together (N.H.T.) to improve this. This classroom action research was conducted in two cycles, each with three meetings. The subjects of the study were all students of class X3. Critical thinking ability data were collected through descriptive tests while learning outcomes included end-of-cycle tests (cognitive) and psychomotor skill observations. The study's findings showed a significant increase in critical thinking skills and students’ learning outcomes. In cycle I, the average percentage of critical thinking skills was 78.67%, increasing to 85.43% in cycle II. The classical completeness of cognitive learning outcomes increased from 59.52% in cycle I to 85.71% in cycle II. Psychomotor completeness also increased from 61.90% (sufficient) in cycle I to 76.19% (good) in cycle II. The combination of guided inquiry and N.H.T. models has proven effective in training students’ thinking and psychomotor skills, especially at the investigation and communication stages of results.